Effect of Climate Change in Years 2006-2019 on Crop Yields in Poland - Gront, Elżbieta Wójcik-; Gozdowski, Dariusz (European Journal of Sustainable Development, 2023)
In recent years, especially since 2005, a substantial increase in temperature has been observed worldwide, including in Poland. Crop production is very important for livestock feeding and food production. In this study, the effect of climate change from 2014 to 2022 on selected crops, especially winter rye yield, was evaluated. The data for the analyses were obtained from the FAOSTAT database and post-registration cultivar trials. The effect of climate change was evaluated for cereals, potatoes, and sugar beets. The trends of crop yields were evaluated using analysis of regression. The results of the study proved a positive correlation between precipitation and crop yield and a negative correlation between temperature and crop yield. The most significant effect of weather conditions was observed in the April-June period. Keywords: climate change, rye yield, forecast.